Separation of Functionalized 5,6-Disubstituted-1,10-Phenanthroline for Dye-Sensitized Solar Cell Applications - Hashem Shahroosvand; Parisa Abbasi; Behrouz Notash; Leyla Najafi (Journal of Chemistry)
5,6-Epoxy-1,10-phenanthroline is used as a convenient starting material for 5-hydroxy-6-Aryl-1,10-phenanthroline ligands containing carboxylic and sulfonic groups useful for further anchoring of the sensitizer on TiO2 for dye-sensitized solar cells (DSCs). Based on the crystal growth of the mixture of products, a convenient separation route for the extension of the p-system on 5,6-disubstituted-1,10-phenanthroline was used to develop a novel series of functionalized 1,10-phenanthroline ligands with electron-withdrawing end-capping group. Also, we report the epoxy opening of 5,6-epoxy-1,10-phenanthroline by aromatic amines stoichiometrically in refluxing water and ethanol in the absence of any catalyst. The dyes were characterized by 1H-NMR, FT-IR, UV-Vis, and X-ray single crystal diffraction analyses. It crystallizes in the monoclinic space group C 2/c, a = 20.920(4) Å, b = 10.340(2) Å, c = 16.187(3) Å, β = 92.30(3)°, V = 3498.6(12) Å3, and Z = 8. The reaction details and features were described in detail.